PENGARUH LIKUIDITAS, PROFITABILITAS, LEVERAGE, KEPEMILIKAN PUBLIK, UMUR PERUSAHAAN DAN UKURAN PERUSAHAAN TERHADAP KELENGKAPAN PENGUNGKAPAN LAPORAN KEUANGAN (Studi Pada Perusahaan Manufaktur Yang Terdaftar Di BEI Periode 2011-2014) - Ajeng Laliddya N, 12.05.52.0105; Maryono, Maryono (Students Journal of Accounting and Banking, 2017)
Financial statement disclosure is essential for the user information. The purpose of this study was to determine the effect of liquidity, profitability, leverage, public ownership, firm age and size of the company on the completeness of the disclosure of financial statements. The population in this research is manufacturing companies listed on the Stock Exchange 2011-2014 period. Samples were taken by using purposive sampling and acquired 35 companies over four years. Mechanical analysis using multiple linear regression analysis. So getting the results of research showing that Profitability, Leverage, Public ownership, company size has a negative effect on the completeness of the disclosure of financial statements. But Age companies and Liquidity positive effect on the completeness of the disclosure of the report. Keywords: Completeness of Financial Statements, Liquidity (CR), Leverage (DER), Profitability, Public Ownership, Age Company and Company Size